Draft genome sequence of Microbacterium sp. strain CH12i, isolated from shallow groundwater in Cape Hallett, Antarctica - Ferreras, Eloy R. (2014)
The Antarctic continent is largely covered by an expansive ice sheet, but it harbors diverse terrestrial and aquatic habitats in the coastal ice-free continental margins. Here we present the draft genome of Microbacterium sp. CH12i, which was isolated from hypersaline, alkaline, and nutrient-rich groundwater from Cape Hallett, northern Victoria Land, Antarctica.